Analysis of Risk Factors Influencing the Incidence of Stroke at RS Otak DR. Drs. M. Hatta Bukittinggi - Sylvia Sylvia; Sumihardi Sumihardi; Yenni Sudita; Ropika Ningsih (International Journal Of Health Science, 2026)
Stroke is one of the leading causes of death and disability worldwide, including in Indonesia, with a national prevalence of 10.9 per 1,000 population. The incidence at DR Brain Hospital Drs. M. Hatta Bukittinggi shows an increasing trend each year, indicating that both modifiable and non-modifiable risk factors have not been optimally managed. The objective of this study was to analyze the characteristics of stroke patients, non-modifiable risk factors, modifiable risk factors, and the most dominant factors influencing the incidence of stroke. This study was conducted at RS Otak Dr. Drs. M. Hatta Bukittinggi from May to August 2025. It was designed using a quantitative method with a cross-sectional design and a descriptive-analytic approach. The study population consisted of 150 individuals, with a sample size of 60 respondents selected through simple random sampling. The instrument used was a questionnaire. Data analysis was performed using univariate, bivariate (Chi-square), and multivariate (binary logistic regression) analyses. The results showed that risk factors significantly associated with stroke incidence included age (p = 0.034), hypertension (p = 0.042), diabetes mellitus (p = 0.030), and dyslipidemia (p = 0.046), smoking (p = 0.035), physical activity (p = 0.035), dietary patterns (p = 0.047) while factors not associated with stroke incidence included sex, family history, heart disease. The most dominant risk factor was dyslipidemia with an OR = 3.378.Based on the findings, primary prevention programs through risk factor screening in the productive age group, education on healthy lifestyles, regular monitoring of blood pressure and blood glucose levels, and health campaigns. Integrated interventions from healthcare providers, government, and the community are expected to reduce stroke incidence and mitigate its long-term impacts.